Recent advances in metathesis-derived polymers containing transition metals in the side chain - Dragutan, Ileana; Dragutan, Valerian; Simionescu, Bogdan C.; Demonceau, Albert; Fischer, Helmut (Beilstein Journal of Organic Chemistry, 2015)
This account critically surveys the field of side-chain transition metal-containing polymers as prepared by controlled living ring-opening metathesis polymerization (ROMP) of the respective metal-incorporating monomers. Ferrocene- and other metallocene-modified polymers, macromolecules including metal-carbonyl complexes, polymers tethering early or late transition metal complexes, etc. are herein discussed. Recent advances in the design and syntheses reported mainly during the last three years are highlighted, with special emphasis on new trends for superior applications of these hybrid materials.
Keywords: advanced materials; metallopolymers; metathesis; ROMP; transition metals